The regulatory role of cyanobacterial High light inducible proteins - Shukla, Mahendra Kumar (Jihočeská univerzita, 2018)
The aim of the thesis was to elucidate the role of High light inducible proteins (Hlips) in the protection/regulation of the biogenesis of photosynthesis machinery. During the project two Hlip proteins (HliC and HliD) were isolated from the cyanobacterium Synechocystis PCC 6803; either as a pure oligomer (HliC protein) or as a small complex with a putative Photosystem II assembly factor Ycf39 (HliD protein). Pigments bound to purified Hlips were analyzed by state-of-art spectroscopic techniques to elucidate the mechanism of thermal energy dissipation. In addition, this work explained the mechanism of how the HliC protein regulates the interaction between chlorophyll synthase enzyme and the Ycf39 protein. This conceptually new mechanism is based on the replacement of HliD dimers in chlorophyll synthase complexes by stress-induced HliD-HliC heterodimers, which changes the affinity of Ycf39 towards chlorophyll synthase.
The regulatory role of cyanobacterial High light inducible proteins
Keywords: Hlips; ChlG; ROS; Ycf39; PSI; PSII; Hlips; ChlG; ROS; Ycf39; PSI; PSII